2003
DOI: 10.1074/jbc.m213058200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection of Adenine-dependent Hairpin Ribozymes

Abstract: Adenine-dependent hairpin ribozymes were isolated by in vitro selection from a degenerated hairpin ribozyme population. Two new adenine-dependent ribozymes catalyze their own reversible cleavage in the presence of free adenine. Both aptamers have Mg 2؉ requirements for adenine-assisted cleavage similar to the wild-type hairpin ribozyme. Cleavage kinetics studies in the presence of various other small molecules were compared. The data suggest that adenine does not induce RNA self-cleavage in the same manner for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 38 publications
2
61
0
Order By: Relevance
“…We quantify the distribution of associated secondary-structural motifs using tree graphs and graph theory measures of size and complexity (particularly, tree diameter and second smallest Laplacian eigenvalue, which are defined in the Materials and Methods section). Our results show that such random RNA pools heavily favor (>90%) simple topological structures like linear stem-loop and low-branching motifs, as confirmed by many known aptamers (Bae et al 2002;Fukusho et al 2002;Khoo et al 2002;Komatsu et al 2002;Ulrich et al 2002;Zinnen et al 2002;Meli et al 2003;Laserson et al 2004). For example, the 25-nt and 40-nt pools are almost completely populated by hairpin and stem-bulge-stem-loop structures.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…We quantify the distribution of associated secondary-structural motifs using tree graphs and graph theory measures of size and complexity (particularly, tree diameter and second smallest Laplacian eigenvalue, which are defined in the Materials and Methods section). Our results show that such random RNA pools heavily favor (>90%) simple topological structures like linear stem-loop and low-branching motifs, as confirmed by many known aptamers (Bae et al 2002;Fukusho et al 2002;Khoo et al 2002;Komatsu et al 2002;Ulrich et al 2002;Zinnen et al 2002;Meli et al 2003;Laserson et al 2004). For example, the 25-nt and 40-nt pools are almost completely populated by hairpin and stem-bulge-stem-loop structures.…”
Section: Introductionmentioning
confidence: 61%
“…Indeed, in vitro selection experiments have revealed novel functional RNAs from random sequence pools, including a wide range of RNA aptamers that bind to particular compounds, such as ATP, antibiotics or proteins, and catalytic RNAs (Wilson and Szostak 1999;Hodgson and Suga 2004); see the collection of several hundred aptamers in the Aptamer Database (http:// aptamer.icmb.utexas.edu). However, an analysis of existing aptamers has shown that RNA sequences isolated from selection experiments tend to have simple topologies (Bae et al 2002;Fukusho et al 2002;Khoo et al 2002;Komatsu et al 2002;Ulrich et al 2002;Zinnen et al 2002;Meli et al 2003;Laserson et al 2004). That is, linear or slightly branched structures occur far more often than highly compact structures.…”
Section: Introductionmentioning
confidence: 99%
“…This result is encouraging, the more so as these constructs represent the first examples of hairpin ribozymes that are allosterically responsive to a small exogenous cofactor. Only one study reported an in vitro selected ATP-dependent hairpin ribozyme (Meli et al 2003) which, however, is very different from our hairpin ribozyme constructs in the sense that ATP does not act as an allosteric effector molecule but is rather required as a catalytic cofactor, similar to guanosine in group I introns. On the other hand, examples of allosteric aptazymes in which small cofactorbinding aptamers were linked to the hammerhead ribozyme via communication modules have shown that small molecules can lead to between 10-and 300-fold induced rate enhancements (Soukup and Breaker 1999b).…”
Section: Design Of the Hinge Region Communication Modulesmentioning
confidence: 93%
“…One of them is also active with imidazole alone. This result leads to very important perspectives (Meli et al, 2003).…”
Section: The Case Of Adeninementioning
confidence: 99%